Two clustered cases of confirmed influenza A(H7N9) virus infection, Beijing - Daitao Zhang; Yi Zhang; Peng Yang; Zhenquan Zhang; Quanyi Wang (University of New South Wales, 2019)
During April 1-8, 2017, a cluster of two laboratory-confirmed A(H7N9) influenza virus infections occurred in Yanqing district, Beijing. None of the 10 close contacts developed symptoms during the medical observation period after their last exposure. Throat swabs collected from close contacts all tested negative for influenza virus. Our study showed that the highly pathogenic avian influenza virus has spread to northern China, where the number of reported cases was relatively small, but the virus is not capable of sustained human-to-human transmission yet. In Beijing, informal live poultry trading in rural areas plays an important role in transmitting highly pathogenic H7N9 virus from poultry to human. Enhanced surveillance in ILI and SARI patients is required to strengthen the case detection capabilities during epidemic periods.